Effects of acupuncture-related intervention on chemotherapy-induced peripheral neuropathy and quality of life: An umbrella review - Mei-Ling Yeh; Chin-Che Hsu; Matthew Lin; Chuan-Ju Lin; Jaung-Geng Lin (Complementary Therapies in Medicine)
Abstracts: Background: Numerous studies have explored the role of acupuncture-related treatments in alleviating chemotherapy-induced peripheral neuropathy (CIPN) and improving the quality of life for patients with cancer, resulting in mixed findings. This umbrella review aimed to synthesize existing systematic reviews (SRs) to deliver an updated assessment of the certainty of evidence concerning the effects of acupuncture-related treatments on CIPN and quality of life among a diverse group of patients with cancer. Methods: This umbrella review considered eligible SRs published on one of nine electronic databases between inception and August 2024. It included adult patients with cancer of any stage who were undergoing chemotherapy. Interventions encompassed acupuncture, either alone or with electrical stimulation or moxibustion, and transcutaneous electrical acupoint/nerve stimulation (TEAS). The outcomes analyzed were changes in CIPN, nerve conduction velocity (NCV), and quality of life. Results: The outcomes were evaluated using data obtained from 14 SRs that demonstrated moderate to high methodological and reporting quality. The findings showed that acupuncture (either alone or combined with electrical stimulation) and TEAS effectively alleviated CIPN symptoms, reduced CIPN pain, improved NCV, and enhanced quality of life. Conclusion: The findings of this umbrella review indicate that these benefits were usually noticeable by the second week of treatment, persisted until the sixth week, and then gradually declined. Sensory nerve recovery occurred more rapidly than motor nerve recovery, often within 1.5 weeks. Although acupuncture combined with moxibustion or acupressure also enhanced patient outcomes, there was insufficient information available for further study analysis.